Slip Effects on Blood Flow in the Presence of a Bell-shaped Stenosed Artery: A Casson Fluid Model - Amit Gupta; Gajendra K. Saraswat; Ravendra Singh (International Journal of Mathematics And its Applications, 2018)
In this a paper, one dimensional Casson fluid flow under the influence of bell shaped stenosed artery have been considered. Analytical and numerical techniques both are carried out to observe this situation. Analytical expressions for axial velocity, plug flow velocity, volumetric flow rate, pressure gradient and wall shear stress has been derived. Numerical techniques have been used to show the effects of yield stress, slip and no slip velocity on these flow variables. The results show that wall shear stress increases as the values of yield stress diminishes and increase in slip velocity reduces the wall shear stress. It is also observed that plug flow velocity increases as slip velocity increases, pressure gradient increases as the slip velocity increases whereas it reduces as yield stress diminishes and axial velocity increases as velocity slip increases.